Sharenting Practices by Millennial Parents as an Effort to Gain Social Recognition - Hidayanto, Syahrul; Athalarik, Fadli Muhammad (Jurnal Komunikasi, 2024)
Unwittingly, when parents share information about their children's lives on social media (sharenting), they need their followers' attention, affection, and a warm attitude to fulfill their emotional needs. This study used a qualitative research approach. Data collection tools in this study were in-depth interviews, literature studies, and observations. The criteria for research informants were parents from the millennial generation who had been actively using social media for more than three years and had a high frequency of social media use. The data analysis used was thematic analysis, which could help researchers capture informants' experiences accessing social media, which researchers then presented through specific themes. Based on the research data processing, in the current digitalization era, the practice of sharing carried out by millennial parents is used to gain social recognition. The results of this study can enrich the discussion on sharing motivation, namely not only in the aspects of self-presentation and social participation but also in the aspect of social recognition.